Willingness to pay for landscape benefits: Examining variation by landscape type in Lower Silesia, Poland - Katarzyna Zagórska; Piotr Krajewski; Marta Sylla; Monika Lebiedzińska; Iga Kołodyńska; Marek Furmankiewicz; Mikołaj Czajkowski (Ecological Indicators)
Like ecosystems, landscapes provide benefits that significantly influence human well-being. However, these benefits are often taken for granted and not accounted for in monetary terms. This project explores how local communities use the surrounding landscapes and the frequency and value of using different types of landscapes for various activities. In a participatory mapping questionnaire, inhabitants of 6 research areas in the Lower Silesia region indicated places where they carry out different activities in selected types of landscapes. Using a discrete choice experiment, we then investigated the public’s willingness to pay for increased provision of landscape services related to the landscape’s spiritual, educational, cultural, aesthetic, and recreational value. Respondents perform the highest number of activities in landscape units where they live. The value of forest landscape is highest, and it is also perceived as multifunctional. There is a significant difference between urban, suburban, and rural respondents, especially in valuing travel time to basic facilities and the importance of place of social integration. Results guide directions for future changes in local landscapes as well as considerations for identifying and valuing landscape benefits in different landscape types.